2021
DOI: 10.3390/medicina57060557
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Cholesterol, Platelet and Cortisol Levels in Patients Diagnosed with Chronic Heart Failure with Reduced Ejection Fraction Groups According to Neutrophil Count

Abstract: Background and Objectives: It is known that neutrophils are involved in the pro-inflammatory processes and thus, can have a great impact on the pathophysiology of heart failure (HF). Moreover, hypercholesterolemia heightens neutrophil production, thereby accelerating cardiovascular inflammation. However, there is a lack of information about the relation of low inflammation to the state of stress, hypercholesterolemia, and pro-thrombotic statement in patients with chronic HF. Therefore, we aimed to determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Several studies have confirmed the safety and effectiveness of remote monitoring of the 24-hour average heart rate and other parameters [ 26 , 27 ]. Some scholars have pointed out that the increase of the 24-hour average heart rate, heart rate variability, and the decrease of patient activity could reflect the clinical status of patients and predict heart failure decompensation events [ 28 ]. The results of other scholars showed that the admission rate of the remote monitoring group was significantly lower than that of the routine follow-up group and the annual admission rate of heart failure per patient in the remote monitoring group decreased from 0.526 to 0.272 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the safety and effectiveness of remote monitoring of the 24-hour average heart rate and other parameters [ 26 , 27 ]. Some scholars have pointed out that the increase of the 24-hour average heart rate, heart rate variability, and the decrease of patient activity could reflect the clinical status of patients and predict heart failure decompensation events [ 28 ]. The results of other scholars showed that the admission rate of the remote monitoring group was significantly lower than that of the routine follow-up group and the annual admission rate of heart failure per patient in the remote monitoring group decreased from 0.526 to 0.272 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that in HFrEF patients, separated into two groups according to neutrophil count (relatively low and high), the CRP and fibrinogen concentrations and monocyte count were higher in the group with a higher neutrophil count [97,99]. These observations are in line with low inflammatory environment in HFrEF patients.…”
Section: Influence Of Monocyte Secreted Cytokines and Inflammatory Readings On Hfref And Hfpef Developmentmentioning
confidence: 73%
“…The deceased persons were of older age, were characterized by worse NYHA functional class, and contained a higher NT-proBNP level [85]. Moreover, the NYHA functional class correlated with total monocyte count and percentage, and the CRP concentration correlated with NT-proBNP level in HFrEF as well [98,99]. Therefore, it could be assumed that the more affected heart muscle is, the higher pro-inflammatory environment is related to the predominance of Mon2 subset in patients with CHF (see Table 3).…”
Section: The Distribution Of Monocytes In Chfmentioning
confidence: 98%
“…Older deceased patients were characterized by a worse NYHA functional class and contained a higher amino-terminal fragment of pro-B-type natriuretic peptide (NT-proBNP) level [ 73 ]. Moreover, the NYHA functional class correlated with the total monocyte count and percentage, and the CRP concentration correlated with the NT-proBNP level in HFrEF [ 80 , 81 ]. Therefore, it can be presumed that the more affected the heart muscle is, the more strongly the pro-inflammatory environment is related to the predominance of the Mon2 subset in patients with CHF (see Table 2 ).…”
Section: Monocytes In Chfmentioning
confidence: 99%
“…It was also shown that among HFrEF patients separated into two groups according to neutrophil count (relatively low and high), the CRP and fibrinogen concentrations and monocyte count were higher in the group with a higher neutrophil count [ 6 , 81 ]. These observations are in line with the low inflammatory environment observed in HFrEF patients.…”
Section: Monocytes In Chfmentioning
confidence: 99%